Literasi Fisik dalam Pembelajaran Kooperatif untuk Penguatan Karakter Siswa - munzir (Jurnal Humaniora Pendidikan (JHP), 2026)
This study aims to develop and evaluate the effectiveness of a cooperative learning model based on physical literacy to enhance students’ character and holistic well-being in secondary schools. The research employed a Research and Development (R&D) approach using the ADDIE model and a quasi-experimental design with a pretest-posttest control group. The participants were secondary school students divided into experimental and control groups. Research instruments included character questionnaires, student well-being scales, observation sheets, and N-gain tests to measure improvement. The results revealed that the physical literacy-based cooperative learning model significantly improved students’ character, particularly in discipline, cooperation, and responsibility. Furthermore, it enhanced students’ holistic well-being, including physical, social, and emotional dimensions. Statistical analysis indicated a significant difference between the experimental and control groups (p < 0.05). Therefore, this model is effective as an innovative learning approach for 21st-century education focusing on character building and holistic student development